IDENTIFIKASI KEANEKARAGAMAN JENIS GASTROPODA DI PANTAI WAITIU, KECAMATAN LEWOLEMA, KABUPATEN FLORES TIMUR - Maria Magdalena Nona Motu Tukan; Maianus Ada Lein; Fitriah Khairul (JURNAL PERIKANAN TROPIS, 2026)
Gastropods are the largest class of Mollusk, and represent one of the important non-fish biological resources. These invertebrates exhibit a remarkable ability to adapt to a wide range of environmental conditions, such as extreme temperatures and salinity levels. Their abundance and diversity are influenced by several factors including environmental conditions, food availability, predation, and competition. This study aims to examine the species diversity of gastropods in the Waters of Waitiu, East Flores Regency. Environmental parameters measured included pH, temperature, and salinity. The study was conducted at one observation station in the intertidal zone. Three line transects were laid perpendicular to the coastline at 50 m intervals. Each transect consisted of three 1x1m2 sampling plots, resulting in a total of nine plots. Gastropod species were identified using gastropod diversity book. The results indicated that the abiotic parameters in Waitiu waters were favorable for gastropod life, with a pH of 7.2, temperature of 28°C, and salinity of 35 ‰. A total of 338 individuals from 14 families and 29 species were recorded, with Hebra Corticata being the most dominant species. The uneven distribution of individuals was influenced by environmental factors affecting the community structure, including dominance, and species diversity. The results of diversity measurements using the Shannon-Wiener index showed an H' value of 2.073, indicating moderate diversity.